Pendampingan Pengembangan Ekonomi Kreatif Berbasis Potensi Lokal di Desa Wisata - Sudiarti, Sri; Rusliana, Nanang; Setyoningrum, Nuk Gurroh; Alam, Alam; Syfa, Raisa Hillia Aini (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This community mentoring activity aims to identify local potential that can be developed into creative economic products and formulate development strategies appropriate to the characteristics of tourist villages. The mentoring approach uses socialization and talk shows. The mentoring results indicate that creative economy development based on local potential, such as arts and crafts, traditional culinary arts, local culture, and ecotourism, can increase community income and strengthen local identity. Recommended development strategies include increasing human resource capacity, collaborating with various stakeholders, utilizing digital technology for promotion, and strengthening village institutions. In conclusion, developing a creative economy based on local potential requires a participatory, sustainable, and adaptive approach to the dynamics of the tourism market